2006
DOI: 10.1007/s00425-006-0299-8
|View full text |Cite
|
Sign up to set email alerts
|

Brittle stalk 2 encodes a putative glycosylphosphatidylinositol-anchored protein that affects mechanical strength of maize tissues by altering the composition and structure of secondary cell walls

Abstract: A spontaneous maize mutant, brittle stalk-2 (bk2-ref), exhibits dramatically reduced tissue mechanical strength. Reduction in mechanical strength in the stalk tissue was highly correlated with a reduction in the amount of cellulose and an uneven deposition of secondary cell wall material in the subepidermal and perivascular sclerenchyma fibers. Cell wall accounted for two-thirds of the observed reduction in dry matter content per unit length of the mutant stalk in comparison to the wildtype stalk. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 37 publications
9
116
2
Order By: Relevance
“…Similarly, the reduced cellulose content in mature stems of the spontaneous maize mutant brittle stalk2 (bk2), disrupted in a gene orthologous to the BC1 gene in rice, goes along with a marked enrichment in lignin deposition, resulting in brittleness of all aerial plant organs (Sindhu et al, 2007). In agreement with its corresponding mutant in rice, bk2 and wild-type plants were indistinguishable in all aspects of plant growth and development (Ching et al, 2006;Sindhu et al, 2007). In brachypodium, the dwarf spaghetti1 (spa1) mutant presents a unique phenotype combining brittleness with increased elasticity of the internodes (Timpano et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the reduced cellulose content in mature stems of the spontaneous maize mutant brittle stalk2 (bk2), disrupted in a gene orthologous to the BC1 gene in rice, goes along with a marked enrichment in lignin deposition, resulting in brittleness of all aerial plant organs (Sindhu et al, 2007). In agreement with its corresponding mutant in rice, bk2 and wild-type plants were indistinguishable in all aspects of plant growth and development (Ching et al, 2006;Sindhu et al, 2007). In brachypodium, the dwarf spaghetti1 (spa1) mutant presents a unique phenotype combining brittleness with increased elasticity of the internodes (Timpano et al, 2015).…”
Section: Discussionmentioning
confidence: 90%
“…So far, several members of the COBRA gene family have been found to be involved in the synthesis of cellulose, which is responsible for the expansion and formation of the cell wall (Schindelman et al 2001;Li et al 2003;Brown et al 2005;Ching et al 2006). In addition, osbc1l4 shows similar mutant phenotype and expression pattern with some cellulose synthase genes (OsCESA4, OsCESA7, and OsCESA9; Tanaka et al 2003).…”
Section: Potential Function Of Osbc1l4mentioning
confidence: 99%
“…AtCOBL9 is required for tip-directed growth in root hair development in Arabidopsis (Parker et al 2000;Jones et al 2006). The rice brittle culm1 (bc1) mutant and the maize brittle stalk 2 (bk2) mutant were found to have mutations in the putative orthologs of AtCOBL4 that affected the mechanical strength of plant tissues and secondary cell wall biosynthesis Ching et al 2006;Sindhu et al 2007). Moreover, recent research has indicated that ZmBk2L1 is required for the root hair development in maize (Hochholdinger et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, hybrid genotypes displayed a greater accumulation of cell wall material (CW) in stem tissues and exhibited a higher proportion of lignin (Lig, Lig/CW) and cellulose (Cel/CW) in their cell walls. Presumably, these structural and constitutional adaptations would lead to improved stalk mechanical-strength; the latter deemed necessary to sustain the increased growth rates and yields typical of hybrid maize (Appenzeller et al 2004;Ching et al 2006). These compositional contrasts, however, did not appreciably alter the prevalent inter-relations that exist between cell wall compositional characters and biomass enzymatic convertibility.…”
Section: Resultsmentioning
confidence: 97%